Pengembangan Subject Specific Pedagogy (SSP) Tematik Berbasis Local Wisdom Untuk Membangun Karakter Hormat dan Kepedulian Siswa SD - Amaliyah Ulfah (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2018)
This study aims at generating possible thematic Subject Specific Pedagogy (SSP) based on local wisdom and examining the results teachers and students perception on the pedagogical approach developed in the preliminary field testing. Drawing upon the notion of research and development by Borg & Gall, this research was conducted through different stages involving information gathering, planning, developing preliminary product, preliminary field testing, and revising. The subjects were a small group of second grade students of SD Muhammadiyah Bodon and SD Muhammadiyah Sidoarum Yogyakarta. Each consists of 10 students. The data gathering instrument consists of product validation, character observation sheets, and teacher assessment sheets. The data gathering instrument consists of product validation tool, character observation sheets, and teachers’ assessment sheets. The SSP product generated in this study consists of lesson plans, teaching materials, worksheets, and expert perception. According to the experts of media, materials, and evaluation, the SSP product is in good categories. First grade teachers result a good score to the syllabus and lesson plans, while the worksheets and evaluation are in very good category. The results from the students responses to the textbooks is 78, which is in very good category, while the students worksheets score 71 which includes in excellent category. Therefore, the developed thematic SSP based on local wisdom can be declared appropriate for use in learning.